SOCIAL-BASED EDUCATION; FOUNDATION OF SOCIAL INTEGRATION OF THE PEOPLE IN SALATIGA - Sutrisna Sutrisna; Zakiyyudin Baidhawy; Waston Waston (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2022)
The purpose of research is to find out the social condition of society, the process of community-based education through social integration of society, and community-based education as the foundation of social integration. This is qualitative research that employed the phenomenological approach conducted in the people of through interviewing and observing the informants, then documenting the information, and after that conducting the focused group discussion. The researcher then validated the data through method and resource triangulations. The interactive techniques of data analysis include data collection, data reduction, data presentation, and concluding. The findings are that the social condition of the people is so plural for its ethnics, religions, races, and cultures. There are institutions and varied social groups with different identities which interacted and adapted to their society to fulfill their social needs to reach balance.  The social integration occurred by adjusting the various components of the living patterns which have the functions synergically.  Society is integrated based on the agreement on norms and values of the society in creating balance, regularity, and harmony.   The components of the social integration which are done by the people among other things are accommodations, coordination, assimilations, and amalgamations; which are aspirations and the potential of the uniqueness of the people and the cultures of the locals. People tried to adjust, cooperate and acculturate among them by respecting others for their diversity and expressions supported by knowledge, open-mindedness, communication, freedom of thought, belief, and conscience and they accept that people are varied in nature. Those social integration components which are done by the people are the social integration practices through social-based education as the manifestation of the education for the society.